LEGAL PROTECTION OF NOTARIES AGAINST THE USE OF THE RIGHT TO RENOUNCE IN CRIMINAL CASES - SETIYA MEGAWATI DEWI (Authentica, 2023)
The Notary as a public official should keep the contents and information in the deed confidential in accordance with the Notary's oath of office in Article 4 paragraphs (1) and (2) and Article 16 paragraph (1) letter f of the UUJN which is realized in the notary's right of denial. However, in criminal cases, the use of the right of denial still cannot be implemented perfectly due to the lack of understanding between the public and the police regarding the right of denial as a notarial obligation and the regulations governing it, resulting in several problems such as errors in the procedure for taking photocopies of deed minutes and summoning notaries as witnesses, expert witnesses and defendants which not only harm notaries but are also considered not respecting the right of denial inherent in notaries. So, on this basis, the legal protection of the notary's right of denial needs to be carried out proportionally. The formulation of the problems in this research are:  (1) How is the Notary's Right of Recusal in Criminal Cases? And (2) How is the Legal Protection of Notary's Right of Recusal in Criminal Cases? The research conducted is normative legal research with a statutory approach, case approach, and conceptual approach. The technique of collecting legal materials is done through literature studies. The data source used is secondary data, which includes primary legal materials and secondary legal materials. Based on the results of the study, notaries can file a right of denial in the court process to carry out the obligation to keep the contents and information of the deed confidential in making the deed. Protection of the notary's right of denial so that Article 66 paragraphs (1) and (3) of the UUJN is fulfilled requires a coaching function by MKN contained in Article 24 paragraph (2) Permenkumham Number 17 of 2021 and the correct procedure for summoning notaries according to Article 28 Permenkumham Number 17 of 2021.Keywords: Legal Protection; Denial Right of Notary; Notary; Criminal.